2005
DOI: 10.1159/000086038
|View full text |Cite
|
Sign up to set email alerts
|

Do Healthy Potential Kidney Donors in India Have an Average Glomerular Filtration Rate of 81.4 ml/min?

Abstract: Background: Until now, a normal reference range for glomerular filtration rate (GFR) in adult Indian potential kidney donors has not been determined and values from a western population are being used as reference. Aim: To determine the reference range of GFR in healthy adult Indian potential kidney donors. Basic Procedures: GFR was measured in 610 (250 male, 360 female, average age 35.16 years) healthy potential kidney donors using the 99mTc-DTPA (diethylenetriamine pentaacetic acid) two-plasma sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
40
6
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 47 publications
6
40
6
1
Order By: Relevance
“…Normal mGFR could be slightly lower in such Asian populations. Different hypotheses to explain such results are lower BSA in this population, low protein diet or different methods to measure GFR [1,32,42,43] . Also in this population, additional research seems necessary.…”
Section: Discussionmentioning
confidence: 88%
“…Normal mGFR could be slightly lower in such Asian populations. Different hypotheses to explain such results are lower BSA in this population, low protein diet or different methods to measure GFR [1,32,42,43] . Also in this population, additional research seems necessary.…”
Section: Discussionmentioning
confidence: 88%
“…21 Srinivas et al, evaluated the performance of serum creatinine based equations to estimate GFR in South Asian healthy renal donors and found that the mean GFR was 95.5±11.6 ml/min. 22 Our study too is comparable with earlier reports and the mean eGFR by CG and MDRD equations was found to be 91.05±15.04 and 86.43±13.61 respectively.…”
mentioning
confidence: 99%
“…In their study, for men >60 years and women >50 years, GFR of 60 ml/min/1.73m 2 is within the normal reference range (12). In another study conducted by Barai et al, on potential kidney donors, it was found that no significant difference in the GFR between males and females in 20-30 or 30-40 year age groups, but significantly higher GFR was observed in females than in males in the age group of 41-45 years, suggesting slow or no progression in females with age (13) . Many authors have showed decline in GFR with age but without taking gender into consideration (1) .…”
Section: Discussionmentioning
confidence: 69%